Exchanges Competition in Listing Services: Evidence for Italian Companies. (8th August 2014) - Geranio, Manuela; Lazzari, Valter
<x xml:space="preserve">Abstract</x> Competition among stock exchanges is growing fast on trading services. Differently, competition for listing securities has so far been minimal, if not absent, especially in Europe. The purpose of this paper is to highlight the monopolistic position that many important and well‐renowned exchanges around the world still maintain on offering and pricing of listing services. We first enlighten the content of listing services. We then quantify fees applied by different exchanges to companies according to their size. We consider both initial and annual fees. Our results show that US exchanges are more expensive for medium‐sized firms whilst EU markets apply higher fees to the largest companies. Up to now, demutualisation of stock exchanges did not lead to the expected reduction of listing fees. Many exchanges, particularly in the EU, are still taking advantage of their exclusive control position by applying premium price policies to the largest companies in order to cross‐subsidise smaller companies.